Penyelesaian Perkara Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial Berdasarkan Prinsip Restorative Justice - Amin, Badia (Universitas Batanghari Jambi, 2024)
The objectives of this study were to: 1) To review and analyse the legal regulation of criminal defamation through social media through Restorative Justice. 2) To know and analyse the legal urgency in the settlement of criminal defamation through Restorative Justice. Which then formulates the problems in this research are: 1) How is the Regulation of the Settlement of Criminal Defamation through Restorative Justice, then, 2) What is the Urgency So that Restorative Justice is treated in the Crime of Defamation? Based on legislation. The results of this study are related to the regulations of Article 310 of the Criminal Code with Article 433 paragraph 1 of the Law of the Republic of Indonesia No. 1 of 2023 concerning the Criminal Code, Furthermore, Law No.19 of 2016 concerning Amendments to Law No.11 of 2008 concerning Information and Electronic Transactions and the Restoration of Restorative Justice in the Crime of Defamation. However, in the process there is no obligation to resolve criminal defamation through Restorative Justice and it is not clearly regulated about the technical implementation in the Article, the regulation of Criminal Defamation through Restorative Justice is because there are no special rules regulated in the Criminal Code, Law No. 1 of 2023 concerning the Criminal Code and the ITE Law in the settlement, however. So that the author wants the rules regarding the Crime of Defamation through Restorative Justice to be revised both in terms of sanctions obtained or losses both material and non-material obtained by victims and the urgency of applying the principles of Restorative Justice to criminal defamation, actually we are talking about equality before the law or often known as equality before the law which is some of the basis for the urgency of defamation so that it is necessary to apply the principles of Restorative Justice including: legal, ethical (justice) purposes in which the author hopes that the application of restorative justice in Indonesia for criminal defamation cases through social media will get more attention from the government by issuing a clearer legal umbrella or regulation that criminal defamation can be resolved with a restorative justice approach, and it is also hoped that all law enforcement parties so that every action taken in the settlement of criminal defamation cases must be guided by applicable rules and not override other public interests, so that in carrying out their duties as law enforcers can provide a sense of justice to the parties to the dispute and the community.